2020
DOI: 10.1021/acsearthspacechem.9b00309
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Clathrate Hydrates in the Ternary H2O–NH3–Cyclopentane System

Abstract: Titan, Saturn's largest satellite, is the only icy moon with a dense atmosphere that is composed mainly of N 2 . Methane, the second most abundant constituent, would be depleted in only 30−100 million years by active photochemistry, suggesting replenishment from Titan's interior. Under Titan's near-surface conditions, clathrate hydrates are the stable form of methane and ice together, making them a likely methane reservoir. Cassini−Huygens observations suggest that ammonia is the main source of Titan's atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…As delineated in the Communication, 1 the preferential destabilization of large cages in sI methane clathrate hydrates formed from freezing of aqueous solutions would be consistent with most observations on the H 2 O–NH 3 –CH 4 , 1 H 2 O–NH 3 –THF, 3,4 H 2 O–NH 3 –CP, 5 and H 2 O–NH 3 –C 2 H 6 6 systems. This mechanism would only be applicable to the temperature-concentration domain where incongruent behaviour of hydrates occurs in presence of an NH 3 aqueous solution.…”
Section: On the Preferential Destabilization Of Large Cages In Si Cla...supporting
confidence: 83%
See 2 more Smart Citations
“…As delineated in the Communication, 1 the preferential destabilization of large cages in sI methane clathrate hydrates formed from freezing of aqueous solutions would be consistent with most observations on the H 2 O–NH 3 –CH 4 , 1 H 2 O–NH 3 –THF, 3,4 H 2 O–NH 3 –CP, 5 and H 2 O–NH 3 –C 2 H 6 6 systems. This mechanism would only be applicable to the temperature-concentration domain where incongruent behaviour of hydrates occurs in presence of an NH 3 aqueous solution.…”
Section: On the Preferential Destabilization Of Large Cages In Si Cla...supporting
confidence: 83%
“…3–5 (1) Incongruent melting/dissociation of the hydrates has been observed in the temperature range ∼200–270 K from optical images, 3 Raman spectroscopy, 3–5 calorimetry, 4,5 and XRD. 5 This implies a persistent equilibrium between fractions of liquid (of varying NH 3 concentration) and crystals that change with temperature as hydrate crystals progressively grow and melt. No changes to the Raman signature or XRD patterns of CP hydrate were observed throughout this process while the ammonia concentration in the remaining liquid changes, which seems irreconcilable with a substantial incorporation of NH 3 inside the structure.…”
Section: On Lack Of Evidence For Incorporation Of Nh3 In Ch4 Hydrates...mentioning
confidence: 99%
See 1 more Smart Citation
“…Jensen et al (2010) and Scarlett et al (2017)]. We study XRD of volatile organics, clathrates and hydrated salt minerals at low temperatures, as a means of exploring the chemistry of planetary materials Cable et al, 2020;Vu et al, 2019;Petuya et al, 2020). The primary instrument we use is a Bruker D8 DISCOVER DaVinci, optimized for powder samples held in capillaries cooled with an Oxford Cryosystems 800 cryostream.…”
Section: Introductionmentioning
confidence: 99%
“…The fast destruction rate of atmospheric methane predicted by pre-Cassini works (Flasar et al 1981;Yung et al 1984) lead scientists to hypothesize the existence of a subsurface source of methane. One potential endogenic source of methane could be the complete or partial dissociation of a clathrate hydrate reservoir (e.g., Lunine & Stevenson 1987;Tobie et al 2006;Choukroun et al 2010;Muñoz-Iglesias et al 2018;Petuya et al 2020) In addition, the possible presence of liquid reservoirs, more or less deeply buried under Titan's surface, has been proposed. For instance, Griffith et al (2012) interpreted dark patches observed in equatorial regions as an emergence of liquid.…”
Section: Introductionmentioning
confidence: 99%